Cloud computing adoption in banking system (UTM) in terms of customers perspectives - Asadi, Shahla (2013)
Cloud Computing is viewed as a technology where enable individuals, businesses and organizations to gain more facilities such as data storage and software services via the Internet. In fact, users rather than investing a large amount of money in purchasing servers and applications are able to rent the computing resources based on their actual demands and on a pay-as-you-go pricing model. Thus, many organizations want to move to Cloud Computing because it provides faster growing areas of the technology. One of the fields that want to move to the cloud computing is the banking field. Theoretically, adoption of cloud-based applications by bank customers, offers a wide range of opportunities for them. However, in practice, most bank customers are yet in doubt whether to adopt banks’ cloud-based applications or still stick on the current banks’ client/server solutions. Barriers such as data privacy and data security are the major hindrance of SaaS adoption. Since the cloud computing helps to store and keep data on remote servers and all the application are used virtually, no need to have own servers. Hence, most the enterprises move toward cloud computing to reduce the cost. Also, banking industry must meet the customer expectations and needs, so they should apply cloud computing and change way to achieve customer demands. The present study discusses about how the adoption of cloud computing assists banking context to meet customer demands and improving their work so efficiently. It is hoped that the results will help the organizations to identify the influence of cloud computing on their transactions .This study was carried out in Malaysia bank in UTM and used a survey by questionnaire to understanding bank customers to adopt new technology. A random sample of 162 respondents, who are aged 22 and older and reside in the Malaysia was recruited through Survey Sampling. Survey data were analysed using the Partial Least Squares (PLS) method with SmartPLS to test for both the validity of the structural model and the measurement model. Finally, we propose a suitable model for the adoption of cloud computing in the banking sector.